MOS-ONLY AUTOMATION TECHNIQUE WITH AN EXEMPLARY MOS-ONLY BP/LP AGILE FILTER DESIGN - (:unkn) unknown (My University, 2017)
0

In this work, a systematic of the automation in the result of the re-obtained small signal parameters based on SPICE and CADENCE-SPECTRE is presented for MOS-Only circuits. Accuracy of the re-obtained parameters was improved by re-formulating in the basis of SPICE and CADENCE-SPECTRE. Moreover, piece-wise polynomial regressive models are presented for gds , g m and Ids conventional expressions. Success of the given MOS-Only design automation based on re-obtained small signal parameters is verified with an exemplary new agile filter.
Keywords: Mühendislik, Elektrik ve Elektronik